2004
DOI: 10.1021/ja046063p
|View full text |Cite
|
Sign up to set email alerts
|

Scandium Half-Metallocene-Catalyzed Syndiospecific Styrene Polymerization and Styrene−Ethylene Copolymerization:  Unprecedented Incorporation of Syndiotactic Styrene−Styrene Sequences in Styrene−Ethylene Copolymers

Abstract: On treatment with 1 equiv of [Ph3C][B(C6F5)4], the scandium half-sandwich bis(alkyl) complex (C5Me4SiMe3)Sc(CH2SiMe3)2(THF) showed extremely high activity (up to 1.36 x 104 kg of sPS/(mol Sc.h)) and syndiospecificity (rrrr > 99%) for the polymerization of styrene at room temperature in toluene. More remarkably, this catalyst system could also effect the syndiospecific copolymerization of styrene with ethylene to yield styrene-ethylene copolymers having syndiotactic styrene-styrene sequences. The styrene conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
221
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(251 citation statements)
references
References 17 publications
18
221
0
3
Order By: Relevance
“…Assignments of the resonances of the copolymer were carried out according to the previous reports. 8,18,[20][21][22][23][24][25] The spectrum of the insoluble part, obtained by TCE extraction of the crude product in Run 11, is shown in Figure 3. In addition to continuous homogeneous monomer sequences consisting of ethylene-ethylene (30.1 p.p.m.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assignments of the resonances of the copolymer were carried out according to the previous reports. 8,18,[20][21][22][23][24][25] The spectrum of the insoluble part, obtained by TCE extraction of the crude product in Run 11, is shown in Figure 3. In addition to continuous homogeneous monomer sequences consisting of ethylene-ethylene (30.1 p.p.m.)…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] However, there have been only limited reports on the synthesis of copolymers containing long syndiotactic styrene-styrene sequences. Hou and co-workers 18 have reported that rare-earth metal-based catalyst systems promote not only the syndiotactic homopolymerization of styrene, but also copolymerization with ethylene, in which the Cp¢Sc(CH 2 SiTMS) 2 /Ph 3 CÁB(C 6 F 5 ) 4 [Cp¢¼C 5 Me 4 (CH 2 TMS)] catalyst system produces a multi-block copolymer consisting of a crystalline SPS part and an ethylene-rich part. Carpentier and co-workers 19 have also reported an ansa-lanthanidocene catalyst that can synthesize a copolymer containing long syndiotactic styrene-styrene sequences separated by a single or a few ethylene units.…”
Section: Introductionmentioning
confidence: 99%
“…图 13 烷烃消除反应合成单茂钇双烷基配合物 Figure 13 Synthesis of mono-Cp yttrium dialkyl complexes via alkane elimination [133] , 从而 开启了单茂稀土阳离子配合物体系催化高分子合成的 篇章. 随后的研究发现单茂稀土阳离子配合物体系还可 以高活性地催化乙烯、1-己烯、苯乙烯、丁二烯和异戊 二烯等均聚, 以及催化乙烯与 1-己烯、丁二烯、异戊二 烯、 降冰片烯等的共聚(图 14) [134] .…”
Section: 单茂稀土金属有机配合物unclassified
“…2c, 4,5 The bis(trimethylsilylmethyl) rare earth complexes bearing other cyclopentadienyl groups such as C 5 H 5 (1a), 6 C 5 MeH 4 (1b), 6 C 5 Me 4 H (1c), 6 1,3-(Me 3 Si) 2 C 5 H 3 (1d), 7 C 5 Me 5 (1eLn), 6 and C 5 Me 4 CH 2 CH 2 PPh 2 (1g-Ln) 8 have also been prepared similarly (Scheme 1). The analogous complexes bearing the cyclopentadienyl ligands with a phosphine or ether side arm such as C 5 Me 4 CH 2 CH 2 PPh 2 (1g) 6 and C 5 Me 4 C 6 H 4 OMe-o (1h) 6 are obtained by the one-pot metathetical reactions of [ScCl 3 (thf) 3 ] with 1 equivalent of the potassium salts of the ligands and 2 equivalents of LiCH 2 SiMe 3 (Scheme 2).…”
Section: Cationic Rare Earth Metal Alkyls As Novel Catalystsmentioning
confidence: 99%
“…The half-sandwich mono-and dialkyl rare earth metal complexes are prepared either by alkane elimination reactions between trialkyl rare earth complexes and the neutral cyclopentadiene derivatives or by metathetical reactions of rare earth trichlorides with the alkali metal salts of the corresponding ligands. 4 ] generates easily the corresponding cationic monoalkyl species, which serve as excellent catalysts for the polymerization and copolymerization of a variety of olefins to yield a new family of polymer materials that show novel properties but are difficult to prepare by other catalysts. The half-sandwich monoalkyl rare earth complexes bearing the silylene-linked cyclopentadienylarylamido ligands act as excellent catalysts for the catalytic dimerization of terminal alkynes, cross coupling of terminal alkynes with isocyanides, and the catalytic addition of terminal alkyne CH, amine NH, and phosphine PH bonds to carbodiimides.…”
mentioning
confidence: 99%